Thermoelectric properties of MgTi2O5/TiN conductive composites prepared via reactive spark plasma sintering for high temperature functional applications. (15th March 2020) - Son, Hyoung-Won; Guo, Quansheng; Suzuki, Yoshikazu; Kim, Byung-Nam; Mori, Takao
Abstract: In this study, thermoelectric properties of MgTi2 O5 -based composites were investigated. 10–30 vol.% TiN were added as a conductive reinforcement phase. MgTi2 O5 /TiN composites were successfully synthesized at 1373 K for 10 min via reactive spark plasma sintering. The present SPS process itself enhanced electrical conductivity of MgTi2 O5 more than 250 times while effectively suppressing thermal conduction by defect engineering. Moreover, compositing further remarkably improved its electrical conductivity, and hence large enhancements in the thermoelectric power factor and ZT value were achieved. The results indicate a new doping technique in MgTi2 O5 and enhancing thermoelectric properties of other insulating oxide materials. Graphical abstract: Image, graphical abstract